Fabrication of carbon electrodes from young coconut fiber by varying the carnonization temperature as a supercapacitor application - Sri Ulina Karo Sekali; Awitdrus Awitdrus (Indonesian Physics Communication, 2024)
Supercapacitors are electrochemical energy storage devices that can provide a higher energy density than conventional dielectric capacitors. The most important component of a supercapacitor cell is the electrodes. In this study, the supercapacitor cell electrodes used are based on young coconut fiber with carbonization temperature variations of 500°C, 600°C, and 700°C. The pre-carbonization process is operated using a temperature of 200°C for 90 minutes, chemical activation using an activating agent ZnCl2 0.5 M, carbonization using N2 gas at various temperatures, and physical activation using CO2 gas at 800°C. The highest density value is the CNL-600 sample with a density loss percentage value of 50.96%. Analysis of electrochemical properties showed that samples with a carbonization temperature of 600°C had the highest specific capacitance values, namely 190.3 F/g using method of the cyclic voltammetry. This shows that the best sample is the sample with a carbonization temperature of 600°C.